Systematic Chromatin Accessibility Analysis Based on Different Immunological Subtypes of Clear Cell Renal Cell Carcinoma - Zhang, Shiqiang; Zheng, Wenzhong; Jiang, Donggen; Xiong, Haiyun; Liao, Guolong; Yang, Xiangwei; Ma, He; Li, Jun; Qiu, Miaojuan; Li, Binbin; Sun, Chunhui; Zhao, Jing; et al. (Frontiers in Oncology, 2021)
BACKGROUND: The tumor immune microenvironment has been the focus of clear cell renal cell carcinoma (ccRCC) research. Chromatin accessibility is critical for gene expression regulation. However, the role of chromatin accessibility in different immunological subtypes of ccRCC based on immune cell infiltration has not been systematically studied. METHODS: 530 patients of the Cancer Genome Atlas Kidney Renal Clear Cell Carcinoma (TCGA-KIRC) data were adopted to estimate immune cell infiltration. 24 types of immune cells were evaluated with single-sample gene set enrichment analysis (ssGSEA). Patients were divided in two clusters based on immune cell infiltration. Systematic chromatin acccessibility analysis was conducted based on two clusters. RESULTS: We compared the relative expression of the immune signature genes among 530 patients of TCAG-KIRC using ssGSEA . Overall survival (OS) analysis revealed 10 types of immune cells were significantly associated with prognosis. Patients were divided into two clusters based on 24 types of immune cell infiltration. Immune cell signals were higher in cluster 1 than cluster 2, as the same with PD-1/PD-L1 signal. Among two clusters 2400 differential peaks were found in TCGA-KIRC Transposase Accessible Chromatin with high-throughput sequencing (ATAC-seq) data. Distribution on 23 chromosomes of differential peaks and prognosis-related immune cells were basically the same. There is no peak distribution downstream. The proportion of peaks upstream of the 5' transcription start site decreases, and both sides of binding regions of the TSS 0.1-1 kb becomes smaller. Enrichment of GO and KEGG of these differential peaks showed remarkably related to the immune regulation in tumor microenvironment. Known motifs and de novo motifs were found by linking motif annotations to different peaks. Survival analysis of related motif transcription factors were prognostic. The GSEA enrichment analysis showed high SP1 expression positively correlates with TGF-beta_signaling, inflammatory response, negatively correlates with TNF-alpha signaling via NFKB. High KLF12 expression negatively correlates with interferon gamma response, IL2-STAT5 signaling, TNF-alpha signaling via NFKB, IL6-JAK-STAT3 signaling. CONCLUSIONS: The abnormality of chromatin accessibility may play an important regulatory role in ccRCC immunity.